$\begin{array}{1 1}(i) 1 \quad (ii) 0 \\ (i) 0 \quad (ii) 1 \\ (i) 1 \quad (ii) 1 \\(i) 0 \quad (ii) 0 \end{array} $

Want to ask us a question? Click here

Browse Questions

Ad |

0 votes

0 votes

- If A is a subset of B, (A $\subset$ B), then P (A $\cap$ B) = P (A)
- $P \large(\frac{B}{A}) =$$ \large (\frac{P(A\;\cap\; B)}{P(A)})$

(i) If A is a subset of B, $(A \subset B), \rightarrow P (A \cap B) = P (A)$

Therefore, $P \large(\frac{B}{A}) =$$ \large (\frac{P(A\;\cap\; B)}{P(A)}) = \frac{P(A)}{P(A)} $$= 1$

(ii) $A \cap B = \phi \rightarrow P (A \cap B) = 0$

Therefore, $P \large(\frac{B}{A}) =$$ \large (\frac{P(A\;\cap\; B)}{P(A)}) = 0$

Ask Question

Tag:MathPhyChemBioOther

Take Test

x

JEE MAIN, CBSE, NEET Mobile and Tablet App

The ultimate mobile app to help you crack your examinations

...